EFFECTS OF SEMANTIC MAPPING, THINK PAIR STRATEGIES AND GPA ON STUDENTS’ DESCRIPTIVE PARAGRAPH WRITING ACHIEVEMENT - Puspita Devi (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2017)
Abstract: The success of the learners in learning a language is their ability to write, and the successful teaching of writing is affected by the strategies employed. The purpose of this research was to investigate the effect of Semantic Mapping (SM), Think Pair Share (TPS) strategies, and Grade Point Average (GPA) on descriptive paragraph writing achievement of Education Technology students of Baturaja University. Thirty-six second semester students were equally divided into two groups. One group was instructed through SM strategy, and the other was taught using TPS strategy. Both groups were classified based on students’ GPA. To determine the effectiveness of the teaching strategies, a writing test of descriptive paragraph was administered. The results showed that both SM and TPS strategies could improve students’ writing achievement significantly. However, SM strategy was more suitable for high level students; meanwhile TPS strategy was more suitable for low level studentThe success of the learners in learning a language is their ability to write, and the successful teaching of writing is affected by the strategies employed. The purpose of this research was to investigate the effect of Semantic Mapping (SM), Think Pair Share (TPS) strategies, and Grade Point Average (GPA) on descriptive paragraph writing achievement of Education Technology students of Baturaja University. Thirty-six second semester students were equally divided into two groups. One group was instructed through SM strategy, and the other was taught using TPS strategy. Both groups were classified based on students’ GPA. To determine the effectiveness of the teaching strategies, a writing test of descriptive paragraph was administered. The results showed that both SM and TPS strategies could improve students’ writing achievement significantly. However, SM strategy was more suitable for high level students; meanwhile TPS strategy was more suitable for low level students. Key words: semantic mapping, think pair share, grade point average, writing